Pengaruh Ulasan Pelanggan Online Terhadap Keputusan Pembelian di Shopeefood - Moh Riski; Didit Darmawan (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
This literature study examines how Online Customer Reviews influence Purchase Decisions at ShopeeFood. To gather more information about the items to be purchased and reduce the risks and negative impacts received when making online purchases, customer reviews can be used as a reference. This literature study aims to analyze and synthesize previous research findings regarding the role of online customer reviews on purchasing decisions and identify other factors that influence online customer reviews on purchasing decisions at ShopeeFood. This study was conducted using a literature reflection method that analyzed various related sources. The results obtained from this study indicate that online customer reviews have a positive and significant influence on purchasing decisions at ShopeeFood.